Analisis Hubungan Jarak Kelahiran dengan Perkembangan Emosi Anak Pertama Usia Remaja di SMK Negeri 1 Cipaku - Nova Sri Rahayu; Dini Nurbaeti Zen; Ana Samiatul Millah; Daniel Akbar Wibowo (Universitas Galuh, 2025)
A short birth interval may reduce the attention and time parents can give to their firstborn child, potentially affecting the child’s emotional development. Children who do not form strong emotional bonds early in life tend to face difficulties in regulating emotions during adolescence. This condition may lead to negative emotional responses such as irritability, anxiety, stress, and even depression. In addition, an unsupportive school environment and peer relationships may worsen emotional challenges. This study aims to analyze the relationship between birth interval and the emotional development of firstborn adolescents. A quantitative approach with a descriptive correlational design was used. The population included all 262 students at SMK Negeri 1 Cipaku, with a sample of 40 adolescents. Data were collected using the Emotion Regulation Questionnaire (ERQ). Regression analysis showed a significance value of 0.000 (p < 0.05), indicating a significant relationship between the variables. The R Square value of 0.605 suggests that 60.5% of emotional development is influenced by birth interval. A t-value of 7.627, greater than the t-table value, supports this result. These findings indicate the importance of proper birth spacing. Parents should be mindful of birth intervals to support the optimal emotional development of their firstborn children.